Long-term activation of hippocampal glial cells and altered emotional behavior in male and female adult rats after different neonatal stressors. (April 2021) - Saavedra, Luis Miguel; Hernández-Velázquez, Martha Guadalupe; Madrigal, Scarlette; Ochoa-Zarzosa, Alejandra; Torner, Luz
Abstract: Early life stress increases the risk of developing psychiatric diseases in adulthood. Severe neonatal infections can also contribute to the development of affective illnesses. Stress and infections both trigger the immediate activation of the neuroimmune system. We compared the long-term effects of neonatal single or combined stress-immune challenges on emotional behavior and glial cell responses in the hippocampus. Male and female Sprague Dawley rats were randomly allocated across four conditions: (1) control + vehicle; (2) maternal separation (MS, 3 h/day on postnatal days [PN] 1–14) + vehicle; (3) control + lipopolysaccharide (LPS, 0.5. mg/kg, PN14); (4) MS + LPS. The rats' behaviors were analyzed from PN120 in males and from PN150 in diestrous females. LPS, but not MS, increased anxiety-like behavior in male rats; however, in females, it increased with both challenges. Depressive-like behavior increased after MS—but not LPS—in males and females. Combined stressors increased depressive-like behavior in both sexes. All stressors promoted microglial activation in CA3 and hilus in males and females. MS and LPS increased the astrocytic density within the male hilus, but LPS only increased it in CA3. MS prevented the rise in astrocytic density with LPS. In females, MS reduced the astrocytic population of the hilus and CA3 areas. Taken together, the behavioral and glial cell responses to early life challenges are sex-dependent and cell-type specific. This suggests a sexual dimorphism in the nature of the adverse event faced. These results have implications for understanding the emergence of psychiatric illnesses. Highlights: Long-term effects of neonatal stress on emotional behavior of male and female rats. Behavioral responses to early life stress depends on the challenge and the gender. Long-term effects of neonatal stress on glial cell responses in the hippocampus. All challenges result in long-term increased activation of hippocampal glial cells. Glial responses to a double challenge may be part of an adaptive response mechanism.